Patients’ needs in breaking bad news for cancers diagnosis: preliminary result - Cuong, Dinh Ngoc; Tue, Pham Tang Tri; Tuat, Huynh Van; Tue, Huynh Thanh; Dung, Ho Xuan (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
Introduction: How to perform a breaking bad news consultation properly with the present circumstances and especially it fits the local people. The way to deliver bad news to cancer patients was studied and practiced widely in the world. Some studies were conducted in Vietnam but not yet in central Vietnam. The people here are quite different in thinking and personality. Hence, they may need and expect consultation differently. The study was performed to note the needs of patients in the breaking bad news of cancer and to explore their own experience of giving bad news. Methods: A cross-sectional study was conducted on 44 cancer patients undergoing treatment at the Hue University of Medicine and Pharmacy hospital in July 2020. Results: Of 44 patients, The age average was 56.73. Male was more prevalent in the study with 61.4%. About 45.5% of patients expected to be explained in a private room and most of them desired to hear the truth at the same time with their family (68.2%), only 4.5% of patients wanted the bad news to be delivered only to their families. One hundred percent of patients preferred their oncologists to explain the bad news. More than 80% of patients wanted you received all at once. Patients were interested in getting information about the diagnosis of cancer, stage of cancer, cost of the treatment, treatment option to be selected and results of clinical studies were less important to them. They mostly wanted the truth to be delivered to them than to the family for most of the information contents given by the researchers. Conclusions: Patients in the study wanted to know the truth but some information was more important than others according to them. They mostly satisfied with the breaking bad news that has been done.